Economic growth in the US and the EU: A sectoral decomposition - Kristian Uppenberg (EIB Papers, 2011)
Drawing on the OECD's structural analysis (STAN) database, this paper contributes to the understanding of European economic growth through a decomposition into employment and productivity, across sectors, and across different time periods and countries. The US productivity surge from the mid-1990s continued for years after the bursting of the dot-com bubble. In the meantime, the EU-15's relative productivity stagnation continued. The sectoral perspective helps us better understand this divergence. While manufacturing remains disproportionally important for aggregate productivity growth, the market services sector, given its size, accounts for the bulk of differences across countries, also within the EU. Market services differ from manufacturing in terms of the nature of innovation and other drivers of growth. This calls for sector-specific analysis when designing growth policy in Europe.
Keywords: 330; Wirtschaftswachstum; Vergleich; Beschäftigung; Produktivität; Industriestruktur; EU-Staaten; USA